MR spectroscopy in heart failure. - Holloway, C; ten Hove, M; Clarke, K; Neubauer, S (2011)
Magnetic resonance spectroscopy (MRS) is an established technique for the non-invasive assessment of myocardial metabolism. MRS is ideal for the evaluation of heart failure, as it allows quantification of the primary energy source for all myocardial cellular functions (ATP), the energy reserve phosphocreatine (PCr), and the creatine kinase reaction, which maintains cellular energy equilibrium. PCr forms the primary ATP buffer in the cell via the creatine kinase (CK) reaction and is involved in transporting the chemical energy from the ATP-producing mitochondria to the ATP-consuming contractile proteins. Using 31phosphorus (31P) MRS, a low cardiac PCr/ATP has consistently been found in patients with heart failure, supporting the hypothesis that the failing heart is energy starved. The use of 1H MRS has allowed the detection of total creatine, which when combined with 31P MRS, provides an in depth examination of the creatine kinase reaction. MRS signals from 31P, 1H, 23Na and 13C, including novel hyperpolarization techniques, have provided considerable insight into the understanding of energy metabolism in the healthy and diseased heart.